RADIOGRAPHIC ASSESSMENT OF IMPACTED THIRD MOLARS: DIAGNOSTIC TOOLS, INDICATIONS, AND CLINICAL RELEVANCE (International Seven Journal of Multidisciplinary, 2023)
The evaluation of impacted third molars—commonly known as wisdom teeth—requires accurate imaging to guide diagnosis, treatment planning, and surgical intervention. Radiographic examinations play a central role in determining the position, angulation, root formation, and proximity of third molars to vital anatomical structures such as the inferior alveolar nerve and maxillary sinus. Panoramic radiography has long been the most commonly used imaging modality due to its comprehensive field of view and low radiation exposure. However, technological advancements have increased the use of cone beam computed tomography (CBCT), especially in complex cases where detailed three-dimensional (3D) information is essential. This paper reviews current radiographic techniques for assessing impacted third molars, comparing their indications, diagnostic capabilities, limitations, and relevance to surgical decision-making. Recent literature emphasizes that while panoramic radiography remains sufficient in most routine cases, CBCT offers superior accuracy in evaluating the spatial relationship between the mandibular third molar roots and the mandibular canal, significantly reducing the risk of inferior alveolar nerve injury. Moreover, periapical and occlusal radiographs may complement panoramic findings in selected cases, offering high-resolution images of specific regions. Guidelines from international dental organizations now support a risk-based approach to imaging, reserving CBCT for cases with high anatomical complexity or unclear findings in conventional images. The purpose of this article is to present an updated overview of radiographic methods available for the evaluation of impacted third molars, highlighting their diagnostic value, clinical indications, and role in minimizing surgical complications. Emphasis is placed on evidence-based imaging protocols that optimize diagnostic yield while adhering to radiation safety principles, such as ALARA (As Low As Reasonably Achievable).